Pengaplikasian Nilai Nilai Ajaran Islam dalam Membentuk Karakter Prajurit Berambisi (Kajian Studi Peperangan Di Masa Nabi) - Nur’ain, Ryan Dzun; Firmansyah, Syahrul Adam (Tanjak: Sejarah dan Peradaban Islam, 2023)
The War of Civilizations during the time of the Prophet Muhammad SAW was an important period in Islamic history. This study analyzes the ethical principles of war, the roles of soldiers and values ​​in conflict. This research method involves analysis of historical documents such as the Koran and Hadith. Military strategies at the time included guerrilla warfare, defensive defense, and diplomacy. The use of horses and weapons such as spears and swords gave the Muslim army speed and strength. The Prophet Muhammad SAW prioritized justice, peace and respect for human rights, which was reflected in peace agreements and protection of non-Muslims. This study provides insight into the wars of this period and their importance in Islamic history and culture.